516PClinical outcomes in elderly patients with advanced non-small cell lung cancer: A prospective multicenter study of the National Hospital Organization in Japan. (24th November 2019) - Shimada, M; Kanazu, M; Shimokawa, M; Saito, R; Mori, M; Tamura, A; Okano, Y; Fujita, Y; Endo, T; Motegi, M; Takata, S; Kita, T; et al.
Abstract: Background: Previous studies have developed risk stratiﬁcation schemas to assess chemotherapy toxicity. However, the geriatric assessment variables that should be used to assess the individual risk of severe chemotherapy toxicity and clinical outcomes in elderly patients remain controversial. Methods: Patients aged ≥70 years with advanced non-small cell lung cancer (NSCLC) who were treated at 24 National Hospital Organization institutions and completed a pre- first-line chemotherapy assessment were included in this study. The assessment included the following: patient characteristics, treatment variables (platinum doublet: PD, single agent: SA, tyrosine kinase inhibitor: TKI), laboratory test values, and geriatric assessment variables. We analyzed the correlations between each factor and clinical outcomes of chemotherapy and overall survival (OS). Results: In total, 348 patients with advanced NSCLC, with a median age of 76 years (range, 70 to 95 years), joined this prospective study. In all patients, the best objective response rate and disease control rate were 35.6% and 81.0%, respectively. The median progression-free survival (PFS) and OS were 6.1 and 16.5 months, respectively. Performance status, treatment variables, and several laboratory test results (anemia, albumin, and C-reactive protein) affected the best response of chemotherapy (p = 0.0249, <0.001, <0.001, <0.001, and <0.001 respectively, between disease control and progressive disease cohorts). These factors also affected the PFS of first-line therapy (5.8 (PD) vs 3.5 (SA) vs 10.5 (TKI), and 2.9 vs 6.4, 2.9 vs 6.3, 3.0 vs 6.5, 3.0 vs 7.0 months respectively, between above or below each cutoff cohort) and OS (13.7 (PD) vs 10.4 (SA) vs 30.6 (TKI), and 7.0 vs 16.8, 6.3 vs 16.8, 6.6 vs 17.8, 6.2 vs 18.1 months, between above or below each cutoff cohort). Conclusions: Performance status, treatment variables, and several laboratory test values independently predicted clinical outcomes of chemotherapy in elderly patients with advanced NSCLC. Clinical trial identification: UMIN000010384. Legal entity responsible for the study: National Hospital Organization. Funding: National Hospital Organization. Disclosure: All authors have declared no conflicts of interest.